Early infection and subsequent insulin dependent diabetes. Issue 5 (1st November 1997) - Gibbon, Caspar; Smith, Trevor; Egger, Peter; Betts, Peter; Phillips, David
Abstract : In a study of 58 children under the age of 16 with insulin dependent diabetes (IDDM) and 172 matched non-diabetic controls, infection during the first year of life was associated with a reduction in diabetes risk (odds ratio 0.81, 95% confidence interval 0.67 to 0.98, per infective episode). Decreased exposure to common infections during infancy may be linked with subsequent IDDM.